MEDIA SINOPSIS CERITA BERASPEK MULTIKULTURAL UNTUK MENINGKATKAN APRESIASI KEBERAGAMAN SISWA DALAM PEMBELAJARAN IPS DI SMPN 2 JATI KUDUS - Fitrianto, Andhika (Program Studi Tadris IPS Fakultas tarbiyah IAIN Kudus, 2019)
The purpose of the research is to describe the facts that causing lack of student diversity appreciation at SMPN 2 Jati Kudus. The next is to clarify that Social Science learning activities using synopsis media with multiculturalism aspect efectively to improve student diversity appreciation at SMPN 2 Jati. The research design used in this study is a qualitative research with a case study approach . Subjects researched are relatively limited , focus of research concerning variable and very broad social dimension because it involves students at once psychological dimensions that are influenced by social and civic life. Implementation of this strategy was observed in the social studies class IX with a synopsis media with multiculturalism aspect. Phenomena analyzed classes ranging from: syllabus, lesson plans, preparation of teaching materials or the use of media to arouse the interest of students to understand the concepts of multiculturalism. Students are also given a set of questionnaire contains an attitude scale that contains student opinions about the diversity of ethnicity, religion in the school and the outside. The data were obtained as follows : the causing factor of a lack of student diversity appreciation at the school because the quality of teaching and learning in these schools. The major factor is the weakness of quality and quantity of social studies teachers. in addition to the surrounding community socio-economic factors behind most impoverished immigrant population. After learning social science with Media Synopsis students begin to understand what is the meaning of the multiculturalism concepts. Students want to hangout and work in group with no barriers of differences culture. When evaluation the results are satisfactory, an average score of 78.6, which means obtaining complete and almost students familiar of multicultural concepts.